Decision Support System Methods: A Review - Megawaty Megawaty; Maria Ulfa (Journal of Information System and Informatics, 2020)
The current information system is the backbone of most companies or agencies. Currently there are various types of information systems including "transaction processing systems (TPS), office automation systems (OAS), knowledge work systems (KWS), management information systems (MIS), decision support systems (DSS), expert systems, groups decision support systems (GDSS), computer support collaborative work systems (CSCW), and executive support systems (ESS) ". Of the various types of information systems that are currently available decision support systems are widely used as aids in making decisions. For this reason, in this study, a study was conducted with a method that can be used in a decision support system. From the study conducted there are three decision support system methods that are often used, namely simple additive weighting (SAW), analytic hierarchy process (AHP), and simple multi attribute rating technique (SMART). The third method is a method that has a weighting value and criteria in the calculation process